VARC-3 defined outcome of valve-in-valve transcatheter aortic valve implantation in stentless compared with stented aortic bioprostheses - Steul, Jean-Honoré; Abdel-Wahab, Mohamed; Stankowski, Tomasz; Haussig, Stephan; Woitek, Felix J.; Gasior, Tomasz; Crusius, Lisa; Knorr, Luise; Müller, Felicitas V.; Fritzsche, Dirk; Kiefer, Philipp; Kappert, Utz; et al. (Clinical research in cardiology, 2025)
Background Valve-in-valve (ViV) transcatheter aortic valve implantation (TAVI) is a viable alternative to redo surgery in selected patients with bioprosthetic valve dysfunction. Most ViV-TAVI procedures have been performed in stented bioprosthetic valves (ST); stentless bioprostheses (SL) lack fluoroscopic markers and could be more challenging for ViV-TAVI. Data on more recent patients applying Valve Academic Research Consortium (VARC)-3 defined outcomes are scarce. We compared patient characteristics, procedural outcomes, and 5-year mortality of patients with SL versus ST aortic bioprosthetic valve failure undergoing ViV-TAVI. Methods Patients undergoing ViV-TAVI between 2007 and 2022 (52.5% of cases after 2015) at 3 German centers were included in this analysis. The co-primary outcome measures were technical success, device success, and early safety defined by VARC-3. Mortality was assessed up to 5 years. Results Overall, 43 (11.8%) SL and 313 (88.2%) ST ViV-TAVI were included. Patients were comparable with regard to age, sex, clinically relevant baseline comorbidities, and surgical risk. Technical success (SL: 83.7% versus ST: 79.9%, p = 0.552), device success (SL: 67.4% versus ST: 54.3%, p = 0.105), and early safety (SL: 74.4% versus ST: 66.5%, p = 0.296) were comparable between groups. The 30-day mortality (SL: 7.0% versus ST: 2.6%, p = 0.136) and 5-year mortality rates (SL: 23.3% versus ST: 24.6%, p = 0.874) were not significantly different between groups. Conclusion SL and ST ViV-TAVI led to comparable short-term outcomes according to VARC-3- defined endpoints and similar mortality rates up to 5 years of follow-up. Graphical abstract VARC-3 defined technical success, device success, and early safety as well as 5-year all-cause mortality in patients undergoing valve-in-valve transcatheter aortic valve implantation (ViV-TAVI) into stentless (SL) compared with stented (ST) failed aortic bioprostheses.